Analysis of One Village One Billion Policy in Increasing Human Growth in Indonesia - Sumardi, Sumardi (Riwayat: Educational Journal of History and Humanities, 2024)
This study is a quantitative study with an explanatory approach, namely an approach that relies on a number of previous studies as the main foundation in this article. The data used in this article is primary data that researchers obtain from credible sources, namely scientific journals, books, websites, and other sources that are commonly used in each study. The data is analyzed by the stages of data